Community Typology and Voting Behavior in Elections: A Political Sociology Perspective - Alwi, Alimin; Ram, St. Wijdanah (Poltanesa, 2024)
Regional head elections (Pilkada) are a democratic process that reflects the social dynamics of society in choosing leaders in regional elections, using a sociological approach to understand the social facts of society. This research aims to analyze typologies that influence voter preferences.  This research uses qualitative methods with a case study approach in several regions that hold regional elections. Data was obtained through in-depth interviews, observation and documentation studies. The research results show that society can be classified into several typologies, such as pragmatic voters, ideological voters, and traditional voters. Pragmatic voters tend to vote based on personal interests or direct benefits, while ideological voters place more emphasis on the candidate's vision, mission and work program. Meanwhile, traditional voters are influenced by cultural factors, kinship, or personal relationships with candidates. Social factors such as campaign intensity, influence of public figures, and access to information also play an important role in shaping voter preferences. These findings show that voting behavior patterns are not only determined by rational aspects, but also by social and cultural values ​​inherent in society.  This research makes an important contribution in understanding voter behavior from a sociological perspective, which can be a reference for stakeholders in designing political strategies that are more inclusive and responsive to community needs. Apart from that, the results of this research can also enrich the study of political sociology, especially in the context of local democracy in Indonesia.